The Use of Artificial Intelligence in Visual Illustrations to Improve Maharah al-Kalam (Arabic Oral Proficiency) - Zikrillah Zikrillah; Koderi Koderi; Guntur Cahaya Kesuma; Ahmad Bukhari Muslim; Syarifudin Basyar (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
Arabic speaking proficiency (maharah al-kalam) continues to face pedagogical challenges, particularly in pronunciation, vocabulary, and contextual comprehension. This study aims to analyze the use of artificial intelligence (AI) in visual illustrations as instructional media to enhance Arabic speaking skills. Employing a systematic literature review method, the study examines 20 selected articles published between 2020 and 2025. The findings reveal that AI-generated visual media significantly improve learners’ vocabulary acquisition, contextual understanding, and engagement in speaking activities. The study implies that AI can be effectively utilized as a pedagogical tool to promote more interactive and context-based Arabic instruction. Its primary contribution lies in proposing a visually oriented AI approach, distinguishing it from previous research that largely focused on text-based applications or chatbot systems.